Debt behavior and money attitude of young urban Malaysian graduates and subjective financial perception - Teo, Boon Chui; Abd Rahim, Faizah; Chuah, Soo Cheng (2011)
The global financial crisis of 2008/2009 brought about decline in social status among the working class. Consequently, it brought family financial issues to the forefront of public discourse particularly in examining how Gen Yers are coping with their financial position in "hard times". This study explores attitudes towards debt and money behavior of young urban Malaysian working graduates. Using quantitative approach, the study surveyed 200 samples of graduates between 21 to 30 years old working in the vicinity of the Klang Valley and Kuala Lumpur. Data was collected using survey approach. Quota sampling was utilized to ensure sample representativeness based on age, occupation, gender and urban ethnic composition. Self-administered questionnaires tapped on money attitudes, debt behaviors, personal money management and subjective perception of current and expected financial and economic condition. Duration of fieldwork took two months. Data was analyzed using statistical techniques such as descriptive statistics, factor analysis ANOVA and regression analysis. Results generated three reliable money attitudes dimensions: budget, power and anxiety money attitude. The young urban Malaysian graduates were budget conscious when spending money. They also viewed money as a source of power and status symbol. On the other hand, they displayed anxiety towards money showing signs of financial insecurity. Debt attitudes generated three debt groups: mild debt and serious debt labeled as pro-debt groups and anti-debt group. Regression analysis showed positive significant relationships between budget and power money attitude with anti-debt behavior. In pro-debt behavior, budget money attitude had a negative significant relationship. Anxiety money attitude was also a significant predictor of pro-debt behavior. Perceptions on current and future subjective financial position were then examined. On their current Subjective financial position, pro-debt groups face difficult situations. However, the debt groups anticipate their future financial position as and country's economy would improve. The study had widespread implications on money and debt management of Gen Verso Having undergone dot.com bust and two financial crises, it is imperative that Gen Yers at the very least buffer themselves financially against economic uncertainties and shocks. It is important that their financial well-being in terms of money for debt and expenses are well managed and they begin to save money. Findings provide support that impact of economic conditions has salient influence on financial well-being of Gen Verso Implications are important for financial literacy at childhood and adulthood. Literature well documents the financial illiteracy of youth, with most reporting that they learn about their finances at home. One of these matters concerned the development of education settings and preparation of family members and educators to affect the financial teaching and learning that are needed to develop fiscally responsible citizens. One aspect of marketing implication is targeting Gen Yers for debt creation by financial institutions. Aided through financial literacy programs offered by the financial services industry, they can be turned into investors. Strategic marketing strategies to attract youthful investors include improving financial websites and develop investment portfolios that meet the needs of Generation Y.